2001
DOI: 10.1186/1297-9686-33-6-635
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic parameters of a random regression model for daily feed intake of performance tested French Landrace and Large White growing pigs

Abstract: -Daily feed intake data of 1 279 French Landrace (FL, 1 039 boars and 240 castrates) and 2 417 Large White (LW, 2 032 boars and 385 castrates) growing pigs were recorded with electronic feed dispensers in three French central testing stations from 1992-1994. Male (35 to 95 kg live body weight) or castrated (100 kg live body weight) group housed, ad libitum fed pigs were performance tested. A quadratic polynomial in days on test with fixed regressions for sex and batch, random regressions for additive genetic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 22 publications
5
32
1
Order By: Relevance
“…Or, as Schulze et al (2002) suggested, to use a multiple trait model using average estimated feed intake of different periods, slopes of different periods, and genetic associations among these traits. Schnyder et al (2001) used a quadratic polynomial random regression model for daily feed intake and indicated that changes of the overall feed intake level are easier to achieve than changes of slope or inflexion of feed intake curves.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Or, as Schulze et al (2002) suggested, to use a multiple trait model using average estimated feed intake of different periods, slopes of different periods, and genetic associations among these traits. Schnyder et al (2001) used a quadratic polynomial random regression model for daily feed intake and indicated that changes of the overall feed intake level are easier to achieve than changes of slope or inflexion of feed intake curves.…”
Section: Resultsmentioning
confidence: 99%
“…Electronic feeders can record detailed information about feed intake behavior in addition to ADFI from group-housed pigs (Von Felde et al, 1996). Knowledge about the shape of feed intake curves is of increasing interest for optimization of lean meat production (Schnyder et al, 2001;Schulze et al, 2002). The same may be true for the shape of feed intake behavior curves as they relate to ADFI.…”
mentioning
confidence: 99%
“…Schulze et al (2002) showed an increase in heritabilities of weekly FI from 0.12 to 0.32 from wk 1 to 9 of test for 2 dam lines of PIC Germany (Genus-PIC, Schleswig, Germany). Furthermore, Schnyder et al (2001) modeled FI of French Landrace and Large White growing pigs with random regression analysis using quadratic polynomials and reported a heritability of 0.09 to 0.25 for this trait during the test period. The above results are in agreement with the heritability found in the current study.…”
Section: Genetic Background Of Feed Intakementioning
confidence: 99%
“…Lower genetic correlations among FI records in Duroc compared with Landrace may reflect breed differences in the development of FI capacity over the test period. Schnyder et al (2001) reported that the genetic covariances between intercept, linear, and quadratic regression coefficients of FI were different between French Landrace and Large White breeds. This is in agreement with the results of the current study.…”
Section: Genetic Background Of Feed Intakementioning
confidence: 99%
“…The observations for each outcome were nested in the 1955 pigs, which in turn were nested in the 43 herds. To estimate the negative effects of the virus infection on growth performance, we used multi-level random-intercept regression models to control for other important predictors, while accounting for clustering or random effects at the pig and herd levels [20]. We used analysis of covariance to determine the statistical significance (P value<0.05 for level of inclusion) of predictors for each of the five outcomes.…”
Section: Methodsmentioning
confidence: 99%